Facilitated spinal neuropeptide signaling and upregulated inflammatory mediator expression contribute to postfracture nociceptive sensitization. Issue 10 (October 2015) - Shi, Xiaoyou; Guo, Tian-Zhi; Wei, Tzuping; Li, Wen-Wu; Clark, David J.; Kingery, Wade S.
Abstract : Abstract: Tibia fracture induces exaggerated substance P (SP) and calcitonin gene–related peptide (CGRP) signaling and neuropeptide-dependent nociceptive and inflammatory changes in the hind limbs of rats similar to those seen in complex regional pain syndrome. Inflammatory changes in the spinal cord contribute to nociceptive sensitization in a variety of animal pain models. This study tested the hypothesis that fracture-induced exaggerated neuropeptide signaling upregulates spinal inflammatory mediator expression, leading to postfracture hind limb nociceptive sensitization. At 4 weeks after performing tibia fracture and casting in rats, we measured hind limb allodynia, unweighting, warmth, edema, and spinal cord neuropeptide and inflammatory mediator content. The antinociceptive effects of intrathecally injected neuropeptide and inflammatory mediator receptor antagonists were evaluated in fracture rats. Transgenic fracture mice lacking SP or the CGRP RAMP1 receptor were used to determine the effects of neuropeptide signaling on postfracture pain behavior and spinal inflammatory mediator expression. Hind limb allodynia, unweighting, warmth, edema, increased spinal SP and CGRP, and increased spinal inflammatory mediator expression (TNF, IL-1, IL-6, CCL2, and nerve growth factor) were observed at 4 weeks after fracture in rats. Fracture-induced increases in spinal inflammatory mediators were not observed in fracture mice lacking SP or the CGRP receptor, and these mice had attenuated postfracture nociceptive sensitization. Intrathecal injection of selective receptor antagonists for SP, CGRP, TNF, IL-1, IL-6, CCL2, or nerve growth factor each reduced pain behaviors in the fracture rats. Collectively, these data support the hypothesis that facilitated spinal neuropeptide signaling upregulates the expression of spinal inflammatory mediators contributing to nociceptive sensitization in a rodent fracture model of complex regional pain syndrome. Abstract : Spinal neuropeptide signaling and inflammatory mediator expression supports nociceptive sensitization in a fracture model of complex regional pain syndrome.